What you need to know when estimating impact functions with panel data for demographic research - Volker Ludwig; Josef Brüderl (Comparative Population Studies (CPoS), 2021)
The estimation of impact functions - that is the time-varying causal effect of a dichotomous treatment (e.g., marriage, divorce, parenthood) on outcomes (e.g., earnings, well-being, health) - has become a standard procedure in demographic applications. The basic methodology of estimating impact functions with panel data and fixed-effects regressions is now widely known. However, many researchers may not be fully aware of the methodological subtleties of the approach, which may lead to biased estimates of the impact function. In this paper, we highlight potential pitfalls and provide guidance on how to avoid these in practice. We demonstrate these issues with exemplary analyses, using data from the German Family Panel (pairfam) study and estimating the effect of motherhood on life satisfaction.
urn:nbn:de:bib-cpos-2021-16en3
Keywords: 300; Fixed effects regression; Impact functions; Motherhood; Negative weighting bias; pairfam; Panel data analysis